1990
DOI: 10.2307/30145487
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Clostridium difficile Toxin-Associated Diarrhea

Abstract: The hospital-wide attack rate for Clostridium difficile-associated diarrhea at our tertiary-care university hospital was 0.02 per 100 patient discharges (0.02%) in 1982, but 0.41% and 1.47% in 1986 and 1987, respectively, with a peak incidence of 2.25% in the fourth quarter of 1987. Hospital antibiotic usage patterns showed concurrent increased use of third-generation cephalosporins, and intravenous vancomycin and metronidazole. Thirty-seven cases selected for study were older than 37 control patients, more li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
70
1
3

Year Published

1997
1997
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(77 citation statements)
references
References 20 publications
2
70
1
3
Order By: Relevance
“…Hospitals with slower bed turnover rates and therefore increased CDAD rates may potentially have increased comorbidity or patient severity of illness. Others have described similar associations when comparing patient-level risk factors for CDAD [11][12][13].…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Hospitals with slower bed turnover rates and therefore increased CDAD rates may potentially have increased comorbidity or patient severity of illness. Others have described similar associations when comparing patient-level risk factors for CDAD [11][12][13].…”
Section: Discussionmentioning
confidence: 86%
“…A number of authors have sought to define patientlevel risk factors that predispose patients to CDAD. Most such analyses have examined patient demographics [7][8][9], comorbid conditions [10][11][12], clinical variables [7,8], and antibiotic treatment characteristics [7,8,13]. Patient-level risk factors have been used to help develop treatment algorithms [14], and may also be useful in developing prevention and control measures.…”
Section: Introductionmentioning
confidence: 99%
“…2,6 Increasing age has been a consistently noted risk factor, with more than tenfold increased risk for patients older than 60 years of age. 11,12 Second, our study only included patients with lymphoma and multiple myeloma in contrast to the other two studies, which included patients with other diagnoses. 2,6 More than half of the patients in the study by Bilgrami et al 6 had solid tumors, while the study by Tomblyn et al 2 included patients with other hematologic malignancies.…”
Section: Discussionmentioning
confidence: 95%
“…Several studies have shown that restriction of clindamycin use was associated with a reduction in nosocomial CDAD cases (Brown et al, 1990;Pear et al, 1994). Other hospitals' rates of CDAD decreased, by at least 50 %, after restricting cephalosporin use (Ludlam et al, 1999;Khan & Cheesbrough, 2003).…”
Section: Control Of Cdadmentioning
confidence: 99%